2019
DOI: 10.3390/ijerph16101766
|View full text |Cite
|
Sign up to set email alerts
|

Pride, Love, and Twitter Rants: Combining Machine Learning and Qualitative Techniques to Understand What Our Tweets Reveal about Race in the US

Abstract: Objective: Describe variation in sentiment of tweets using race-related terms and identify themes characterizing the social climate related to race. Methods: We applied a Stochastic Gradient Descent Classifier to conduct sentiment analysis of 1,249,653 US tweets using race-related terms from 2015–2016. To evaluate accuracy, manual labels were compared against computer labels for a random subset of 6600 tweets. We conducted qualitative content analysis on a random sample of 2100 tweets. Results: Agreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…First, a random 1% sample of publicly available tweets was collected from November 2019 to June 2020, using Twitter’s Streaming Application Programming Interface (API). Details of the data collection process including the full keyword list have been previously published [ 21 ]. We restricted our analyses to English language tweets from the United States with latitude and longitude coordinates or other “place” attributes that permitted the identification of the state where the tweet was sent.…”
Section: Methodsmentioning
confidence: 99%
“…First, a random 1% sample of publicly available tweets was collected from November 2019 to June 2020, using Twitter’s Streaming Application Programming Interface (API). Details of the data collection process including the full keyword list have been previously published [ 21 ]. We restricted our analyses to English language tweets from the United States with latitude and longitude coordinates or other “place” attributes that permitted the identification of the state where the tweet was sent.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, there were 15,683,909 tweets about black people, 1,801,780 about Asian people, 1,577,568 about white people, 1,512,566 about Hispanic people, and 1,274,827 about Middle Eastern people ( Table 2 ). We have previously examined the emerging themes of tweets using race-related keywords [ 41 ]. Briefly, for negative sentiment tweets, tweets ranged from complaints about hassles in daily life (eg, “I hate when ppl Try to Join a Sport all late like niggah you didn't put in the work I did”) to race-related insults using derogatory language (eg, “Middle Eastern/Arabic accents piss me off more than most things”) and rare tweets expressing hostility or mentioning violence (eg, “if they are carrying a Mexican flag in Az.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the emotional tone of the tweet may display a negative sentiment, but it does not necessarily express a prejudiced statement, which was also common in our data. Our prior research indicated that prejudiced tweets can be distinct from the sentiment of the tweet [ 41 ]. For some tweets, negative sentiment also expressed negative racial attitudes or prejudiced beliefs (eg “Middle Eastern/Arabic accents piss me off more than most things.”) However, there were also negative sentiment tweets using race-related terms that did not express prejudiced beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Tweets were classified into five main racial/ethnic categories: Asians, Arabs, Blacks, Latinos, and Whites according to the keywords used. Details of the data collection process including the full keyword list have been previously published ( Nguyen et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Research examining area-level racial sentiment is in its infancy. Building on prior research, our measure offers new, cost-efficient data sources for characterizing area-level racial sentiment ( Nguyen et al, 2019 ). The measure demonstrated associations with adverse birth outcomes (T. Nguyen et al, 2020 ; Nguyen et al, 2018 ) and cardiovascular outcomes ( Huang, Huang, Adams, Nguyen, & Nguyen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%